A Review of On-Site Wastewater Treatment Systems in Western Australia from 1997 to 2011. (19th April 2015) - Gunady, Maria; Shishkina, Natalia; Tan, Henry; Rodriguez, Clemencia
Abstract : On-site wastewater treatment systems (OWTS) are widely used in Western Australia (WA) to treat and dispose of household wastewater in areas where centralized sewerage systems are unavailable. Septic tanks, aerobic treatment units (ATUs), and composting toilets with greywater systems are among the most well established and commonly used OWTS. However, there are concerns that some OWTS installed in WA are either performing below expected standards or failing. Poorly performing OWTS are often attributed to inadequate installation, inadequate maintenance, poor public awareness, insufficient local authority resources, ongoing wastewater management issues, or inadequate adoption of standards, procedures, and guidelines. This paper is to review the installations and failures of OWTS in WA. Recommendations to the Department of Health Western Australia (DOHWA) and Local Government (LG) in regard to management strategies and institutional arrangements of OWTS are also highlighted.